2011
DOI: 10.1097/mnm.0b013e32834508b3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of somatostatin receptors in large cell pulmonary neuroendocrine carcinoma with 99mTc-EDDA/HYNIC-TOC scintigraphy

Abstract: Within a rather large series of LCNEC, the primary tumor showed an uptake of Tc-TOC in all cases, whereas some metastases did show Tc-TOC uptake and some others did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…An analysis of somatostatin receptor scintigraphy in pulmonary LCNEC was done in 26 patients with technetium-99m ethylene diamine-diacetic acid/hydrazinonicotinyl-Tyr3octreotide (Tc-TOC). This study found that 100% of primary lesions showed uptake of Tc-TOC while 84% of metastases were visualized (as compared to conventional imaging) (149). Another study retrospectively examined 26 patients with primary pulmonary LCNEC and compared them to 40 patients with adenocarcinoma.…”
Section: Future Directionsmentioning
confidence: 95%
“…An analysis of somatostatin receptor scintigraphy in pulmonary LCNEC was done in 26 patients with technetium-99m ethylene diamine-diacetic acid/hydrazinonicotinyl-Tyr3octreotide (Tc-TOC). This study found that 100% of primary lesions showed uptake of Tc-TOC while 84% of metastases were visualized (as compared to conventional imaging) (149). Another study retrospectively examined 26 patients with primary pulmonary LCNEC and compared them to 40 patients with adenocarcinoma.…”
Section: Future Directionsmentioning
confidence: 95%
“…And optimized as follows: in a rubber-sealed vial, 10 μg of peptide was incubated with 1 mL of EDDA/tricine solution (20 mg tricine, 10 mg EDDA in PBS buffer, pH 6-7), 1 mL of 99mTcO 4 solution (450 MBq) and 20 µL of tin(II) solution (10 mg of SnCl 2 in 10 mL of 0.1 N HCl) for 15 min at 100 °C. Reactions were then cooled down at room temperature (Decristoforo et al 2006;Nocun et al 2011). After that, the mixture was purified by Sep-Pak C-18 cartridges (Waters Company, America) following the protocol of previous descriptions.…”
Section: Peptide Synthesis and Radioactive Labelingmentioning
confidence: 99%
“…At the beginning of this century, two new 99m Tc-labelled SST analogues were introduced: [ 99m Tc]Tc-N4-[Tyr3] Octreotate (Demotate ® , POLATOM, Otwock, Poland) and [ 99m Tc]Tc-EDDA/HYNIC-[Tyr3] Octreotide (Tektrotyd ® , POLATOM, Otwock, Poland) [11], both of which are widely used in clinical practice with major advantages over [ 111 In]In-Octreotide [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%